Mechanical Assessment of GKN’s Outlook of Next Generation’s Aircraft Engines - Gustafsson, Martin (My University, 2019)
Boeing New Midsize Airplane is a potential future midsize airplane that also will feature a new aero engine. GKN has conceptually designed a new aero engine based on engine performance and component design data, called the Notional Engine, and the next step is to evaluate the overall architecture from a mechanical viewpoint. This project aims to give an overview of the loads acting on an aero engine and to provide a finite element model of the Notional Engine. The finite element model will thereafter be evaluated to see how well it represents the actual engine. A general overview of the loads was obtained by studying previous whole engine mechanical models at GKN and by conducting a literature study. The finite element model was implemented into OptiStruct where maneuver load cases were simulated. A stiffness correlation study was performed at selected parts of the engine to see how well the finite element model, which consists mostly of shell elements, represents the component geometry that it builds upon. The results show that modelling with higher fidelity is needed to accurately represent the geometry that the engine builds upon. However, the results from this project can be used as a building block for future work and is a major leap forward towards accurate mechanical analyses of the Notional Engine.
Keywords: GKN; Finite element; Aero engine; Loads on an aero engine